1984
DOI: 10.1159/000260819
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Secondary Caries around Restorations in Roots

Abstract: The aim of this investigation was to evaluate differences in development of caries-like lesions around dental filling materials in root surfaces. Acidified gels were used to induce the lesions in 75 roots of extracted premolars. Three different exposure times were used. The results showed that wall lesions developed at different speeds, but with a prolonged gel time all cavities showed wall lesions. Significantly smaller lesions were found around cavities filled with fluoride-releasing filling materials; prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…These studies, however, used undialyzed gel and much longer immersion periods in the gels, although the results are similar. Our findings are also in line with those of DERAND & JoHANSON (19) who reported slight inhibitory effect on artificial root lesions when testing an amalgam eontaining 0.5% SnF, in an acidified gel model.…”
Section: Discussionsupporting
confidence: 92%
“…These studies, however, used undialyzed gel and much longer immersion periods in the gels, although the results are similar. Our findings are also in line with those of DERAND & JoHANSON (19) who reported slight inhibitory effect on artificial root lesions when testing an amalgam eontaining 0.5% SnF, in an acidified gel model.…”
Section: Discussionsupporting
confidence: 92%
“…Also in vitro, demineralization around glass iono mer is markedly reduced [Derand and Johansson, 1984;Hicks et al, 1986;Hattab et al, 1989;Forss and Seppa, 1990]. It has been suggested that the main reason for this is the influence of fluoride released by glass ionomer mate rial on the demineralization process.…”
mentioning
confidence: 99%
“…It is important that the consequences of microleakage are minimized by all available means at our disposal. The cariostatic effect of glass ionomer, due to the release of fluorides, is one of the major methods (Derand & Johanson, 1984;Swartz, Phillips & Clark, 1984). The present study evaluated the favourable combination ofthe 'sandwich' technique that would minimize marginal microleakage at the enamel (occlusal) margin and particularly at the cervical (below the cemento-enamel junction) cavosurface line angle.…”
Section: Discussionmentioning
confidence: 99%